2001
DOI: 10.1001/archopht.119.10.1518
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Toxicity of Intravitreal Chemotherapy for Primary Intraocular Lymphoma

Abstract: To investigate the pharmacokinetics and toxicity of intravitreal chemotherapeutic agents in the rabbit eye for the potential treatment of primary intraocular lymphoma and other intraocular malignancies. Methods:The ocular pharmacokinetics of intravitreal methotrexate sodium (400 µg) was studied in 10 New Zealand white rabbits, and a single-compartment, firstorder elimination model was used to calculate the drug half-life. With the use of these data, a treatment schedule using serial injections of intravitreal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 33 publications
(36 reference statements)
5
52
2
1
Order By: Relevance
“…Velez et al [65] showed no ERG abnormalities after intravitreal injection of 2 g/0.1 ml. On the other hand, 4 g/0.1 ml caused a decrease of 34.5% in the b-wave, and with 8 g/0.1 ml, the b-wave was absent.…”
Section: Antiviral Agentsmentioning
confidence: 94%
See 2 more Smart Citations
“…Velez et al [65] showed no ERG abnormalities after intravitreal injection of 2 g/0.1 ml. On the other hand, 4 g/0.1 ml caused a decrease of 34.5% in the b-wave, and with 8 g/0.1 ml, the b-wave was absent.…”
Section: Antiviral Agentsmentioning
confidence: 94%
“…MTX affects cells in the S phase of the cell cycle [69] , and it is most effective against rapidly proliferating cells. MTX is mostly used in combination with other antineoplastic agents in the treatment of the ocular neoplasias [65,69,70] .…”
Section: Antiviral Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some are too complex for clinical practice or vitreous concentrations of chemo therapeutic do not reach effective levels and are unstable 1 . Another described treatment is intravitreal transscleral injection of chemotherapeutic agent 4,5 . No serious com plications have been found to date but tumor dissemi nation in human retinoblastoma was demonstrated by subsequent fine needle biopsy or pars plana vitrectomy 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of experimental models is important as there are many difficulties involved in getting intraocular tissue from patients' eyes, including technical and ethical issues. Experimental models are important for the development of new therapeutic agents as they are useful to evaluate the efficacy and toxicity of systemic and intravitreous drug delivery, such as antibiotics (3)(4)(5) , corticosteroids (6,7) , immunosuppressive drugs (8,9) , and more recently anti-VEGF (10,11) , and biological agents (e.g., tacrolimus, sirolimus, etanercept, infliximab, adalimumab, and rituximab) (12)(13)(14)(15)(16)(17)(18)(19) . The aim of this paper is to review the most used experimental autoimmune ocular inflammatory diseases models used in Ophthalmology and their most important aspects.…”
Section: Introductionmentioning
confidence: 99%